A neural circuit for gastric motility disorders driven by gastric dilation in mice - Wang, Xi-yang; Chen, Xiao-qi; Wang, Guo-quan; Cai, Rong-lin; Wang, Hao; Wang, Hai-tao; Peng, Xiao-qi; Zhang, Meng-ting; Huang, Shun; Shen, Guo-ming (Frontiers in Neuroscience, 2023)
Symptoms of gastric motility disorders are common clinical manifestations of functional gastrointestinal disorders, and are triggered and exacerbated by stress, but the neural pathways underpinning them remain unclear. In a functional magnetic resonance imaging experiment on humans, we found the functional connectivity between the hypothalamus and the brainstem was enhanced in subjects with gastric dilation following electroacupuncture intervention. To reveal this phenomenon, we set-up a mouse model by gastric dilation in which the gastric dynamics were assessed by installing strain gauges on the surface of the stomach. The neural pathways associated with gastric motility disorders were investigated by behavioral tests, electrophysiology, neural circuit tracing, and optogenetics and chemogenetics involving projections of the corticotropin-releasing hormone (CRH) from the paraventricular nucleus of the hypothalamus (PVN) to acetylcholine (ChAT) neurons in the dorsal motor nucleus of the vagus (DMV). Gastric dilation increased PVNCRH neuronal activity. The inhibition of PVNCRH neuronal activity alleviated gastric motility disorders induced by gastric dilation. The PVNCRH neuronal projections innervated DMVChAT neurons and modulated activity of the PVNCRH→DMVChAT pathway to alleviate gastric motility disorders induced by gastric dilation. These findings indicate that a novel PVNCRH→DMVChAT pathway may mediate at least some aspects of gastric dilation (GD) related gastric motility, and provide new insights into the mechanisms by which somatic stimulation modulates the physiological functions of internal organs and systems.